Patients' and general practitioners' satisfaction with information given on discharge from hospital: audit of a new information card. Issue 6714 (16th December 1989) - Sandler, D. A.; Heaton, C.; Garner, S. T.; Mitchell, J. R.
Abstract : OBJECTIVE–To determine the attitudes of patients discharged from hospital and their general practitioners to a new information card giving details about admission, diagnosis, and treatment and to assess the completeness of the information on the card. DESIGN–Consecutive patients discharged from the care of three consultant physicians over 16 weeks. SETTING–One general medical ward in a large teaching hospital. PATIENTS–A total of 275 consecutive discharges of 258 patients were studied. The mean age of patients was 60 years and mean duration of admission five days. INTERVENTION–At discharge from the ward all study patients received an information card and a copy of the card in the form of an interim discharge letter to be delivered to their general practitioner. Patients and general practitioners were asked to complete a questionnaire giving their views on the legibility, helpfulness, quality, and quantity of the information they received. Copies of all the information cards were scrutinised for completeness. MAIN RESULTS–The results were based on 208 (76%) forms returned by patients and 214 (78%) forms returned by general practitioners. Information was considered very helpful or quite helpful according to 170 (83%) forms from patients and 197 (92%) forms from general practitioners; sufficient information was provided according to 160 and 182 forms. Most patients and nearly all general practitioners thought it was a good idea to provide this information for patients at discharge. According to 125 forms from patients and 188 from general practitioners the information card was very easy or quite easy to read; 155 patients had read it at least twice and 149 were likely to refer to it again. OTHER RESULTS–The written information about the patient, the diagnosis, and what the patient had been told was generally well completed, although the date of discharge was omitted from 42 (15%) cards. Details of drugs prescribed at discharge were generally thorough. CONCLUSIONS–Giving an information card to all patients at discharge was feasible and favoured by most patients and their general practitioners. Having made minor changes in design, we think that we have produced an information card that is a convenient size and will improve communication between patients, their general practitioners, and hospital doctors. We now issue this card routinely to all patients discharged from our ward and hope that it might be widely adopted.